Legal aspects of protection of women’s rights from domestic violence under the legislation of Hungary and Ukraine - Golovko, Liudmyla; Shynkaruk, Nataliia; Popova, Olena; Melnyk, Anna; Medvedska, Viktoriia (Interacción y Perspectiva, 2023)
The purpose of the article is to reveal the experience of Hungary and Ukraine in the legal regulation of protection of women from domestic violence, identify positive experience that has proven itself in practice and is therefore worth following in other states. To achieve this purpose, general and special scientific research methods were used, in particular dialectical, systematic and comparative legal methods. The article is devoted to the analysis of the features of legal protection of victims of domestic violence in two Eastern European states (Hungary and Ukraine). An analysis of the formation of legal regulation of combating domestic violence in Ukraine and Hungary was carried out, with a special emphasis on the protection of women’s rights. A comparative analysis of the legislation of Ukraine and Hungary in the field of combating domestic violence was carried out and the strengths and weaknesses of this regulation were identified. A gradual improvement of legal regulation in this area was revealed in both countries, but also problems in the implementation of legislation were found.